L’esigenza di cura nei servizi di salute mentale: una prassi terapeutica - Carlotto, Alessandra (Il sogno della farfalla, 2020)
Health policy is taking a new direction towards a global definition of well-being, mental health together with a significant revaluation of human rights. The author proposes a critical and constructive analysis of the current Italian mental health system. Moreover, the article highlights the need and potential effectiveness of introducing a psychotherapeutic practice as a primary treatment for psychotic patients in the public mental health service. Based on Massimo Fagioli’s Human Birth Theory, this practice is centred on the inter-human relationship between psychotherapist and patient, in which the pathology is addressed on three different levels: unconscious, consciousness and behaviour. The aim of this therapy is to cure and recreate the original healthy state at birth. In this context medications and rehabilitation are an important yet secondary means of support, while psychotherapy represents the main tool of psychiatric intervention in psychotic patients.